“Tramando arames, pedras e fios”: espaço e estigma no trabalho de um artista - Carolina Dalla Chiesa; Pedro Henrique de Gois; Gabriela De Luca; Neusa Rolita Cavedon (Ciências Sociais Unisinos)
This article aims at evidencing the stigmas related to the work developed by a street artist, specifically, in the centre of the city of Porto Alegre, a crowded spot typical of large cities where the degradation and revitalization of the space turn fears and sociability into mediators for the interactions that happen there. In order to reach this objective, we base the study mainly on the notion of stigma and the transformations that happen over time in the artisan’s and artist’s work, and look at space from an anthropological perspective, bearing in mind the meanings attributed to it. We aim at addressing the relationship between work, space and interactions established with the artisan’s activity through an ethnographically inspired study utilizing techniques such as interview, observation and filming. As part of the analysis, we argue that the visibilities and invisibilities constituted in the interactions with the artist are related to the dimension of the work linked to the space where it is developed, producing a stigma – at a higher or lower level – from the perspective of those who see and those who are seen. Both the artist and the work are judged and identified relationally. In this situation we studied, it is possible to see the labor activity being established in a relational manner and, moreover, and craftsmanship being understood as stigmatizing or a pejorative term by the subject themselves and by the passersby. Keywords: craftsmanship, street, stigma.inspired study utilizing techniques such as interview, observation and filming. As part of the analysis, we argue that the visibilities and invisibilities constituted in the interactions with the artist are related to the dimension of the work linked to the space where it is developed, producing a stigma – at a higher or lower level – from the perspective of those who see and those who are seen. Both the artist and the work are judged and identified relationally. In this situation we studied, it is possible to see the labor activity being established in a relational manner and, moreover, and craftsmanship being understood as stigmatizing or a pejorative term by the subject themselves and by the passersby.